The dog stars : a novel - Heller, Peter, 1959- (Vintage Contemporaries, 2013)
Surviving a flu pandemic that has killed everyone he knows, a pilot establishes a shelter in an abandoned airport hangar before hearing a random radio transmission that compels him to risk his life to seek out other survivors.